Etiology of Post-Traumatic Lower Extremity Amputations and Disability Evaluation - Ünal, Volkan; Yurtseven, Ayşe; Erdoğan, Mustafa; Anolay, Nezih; Özgün Ünal, Esra; Baklacıoğlu, Ferruh (The Bulletin of Legal Medicine, 2016)
Objective: Cutting of all or a part of a limb or digit of the body by surgery is called amputation. Amputations mostly occur after traumas and it is known that 80-85 % occurs at the lower extremities. With this study it is aimed to present the traumatic amputation cases which were sent by the courts to the 3rd Specialization Board of the Council of Forensic Medicine, etiology of the amputation, relation between trauma and amputation level. If there are any predisposing factors to amputation, evaluation of disability and precautions to be taken.Materials and Methods: The cases which were sent to the 3rd Specialization Board of the council of forensic Medicine between 01.01.2014-31.12.2014 for evaluation of disability were retrospectively analyzed and traumatic lower extremity amputations included to the study.Results: Totally 119 lower extremity amputation cases were found. Majortiy of then cases (n=100) were male and 19 were female. Most common reason of amputation were traffic accidents (n=60) and the second common reason were occupational accidents (n=31). Proximal level of the cruris is the most common level of amputation (n=32) and the second is the finger (n=21) level.Conclusions: Amputations are important for creating need to the prosthesis and for being subject for individual or intuitional compensation claims. After the case becomes a legal issue individuals take payments on disability rates. Prevention and health management of these cases are importantfor reducing compensation payments.Keywords: Trauma, Disability, Forensic Medicine, Compensation, Amputation, Accident.
Keywords: trauma; disability; forensic medicine; compensation; amputation; accident